(3NdGUI eG aj GdGfJUGQ ef GdELeGYGJ hGdCbhGd hGdCOdIs - (3CHh GdbGSe, GdTQja GdeQJVj, Ydj Hf GdMSjf Hf ehSi, J (B436(3g` (B1044(3e(B)s ((3cGTa GdZWGAs)
(3ChdgG (B:s
(3ChdgG(B: (3cJGH GdWgGQI, hajg eSGFd(B: (3CMOgeG eeG TfY Hg Ydi GdEeGejI hXf Cfg dG ehGab dge ajg bhdge(B: (3Ef GdeGA EPG HdZ cQGs
(3BNQgG (B:s
(3BNQgG(B: (3hdGdG eYGQVI Hjf BjI GdehGQjK hBjI GdhUjI hGdYed HgeG LejYG eecf hCeG GdCNHGQ aEf SdeJ ef (B... (3agj Xfhf dG (B.. (3dgG Gdjbjfs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe, L(B4: 278s
(3GdPQjYI, L (B2: 203s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3abg GdePGgH GdCNQis